Investigating Potential Links Between Fine-Grained Components in Loess and Westerly Airflow: Evidence From East and Central Asia - Li, Yue; Song, Yougui; Fitzsimmons, Kathryn E.; Dave, Aditi K.; Liu, Yuming; Zong, Xiulan; Sun, Huanyu; Liu, Huifang; Orozbaev, Rustam (Frontiers in Earth Science, 2022)
Loess is a ubiquitous, silty aeolian sediment common across the semi-arid to subhumid regions in Northern Hemisphere. As such, the physical characteristics of loess sediment, such as modal grain-size and quartz crystallinity index, have the potential to inform us about dust transport pathways and corresponding atmospheric circulation responsible for entrainment, transport and deposition. In this paper we combine detailed granularity analyses and non-parametric end-member modelling with investigations of the quartz crystallinity index of three loess deposits extending from East through to Central Asia, with the aim of identifying dust transport processes and the climate subsystems responsible for them. We find marked differences in the grain-size characteristics of Eastern and Central Asian loess. Given potential linkages of fine particles to the westerly jet stream, here we focused on the fine-grained end-members in the loess. The fine-grained components of the Central Asian – Bishkek (BSK) and Chashmanigar (CMG) – loess may be derived from individual particles carried at high altitude by major climate subsystems such as the westerlies. However, similar quartz crystallinity indexes of fine- and coarse-grained components in the Central Asian loess indicated that surface-level wind strength might influence on the releases from proximal-sourced regions and abundances in the upper atmosphere for the fine particles. By contrast, the fine-grained component of the East Asian [Fanshan18 (FS18)] loess seems to yield physical similarities to the Tertiary Red Clays underlying many loess stratigraphy, and has been interpreted to relate to transport associated with the East Asian winter monsoon. It was further supported by quartz crystallinity indexes of the <16 μm fractions in the FS18 loess basically consistent with those of the deserts in North China, highlighting the near-surface northwesterly winter monsoon as the dominant transport dynamics of fine-grained dust. In addition, comparisons of quartz crystallinity indexes of fine-grained components between the East and Central Asian loess also suggest that variations in fine particles within the loess might not be related to transport by the higher-level westerlies, in disagreement with the previous model. Therefore, our results indicate that variations in fine-grained end-members in loess are difficult to reliably document the variabilities of higher-level westerlies.